2011
DOI: 10.1007/s12035-011-8166-4
|View full text |Cite
|
Sign up to set email alerts
|

Collapsin Response Mediator Protein-2: An Emerging Pathologic Feature and Therapeutic Target for Neurodisease Indications

Abstract: Collapsin response mediator protein-2 (DPYSL2 or CRMP2) is a multifunctional adaptor protein within the central nervous system. In the developing brain or cell cultures, CRMP2 performs structural and regulatory functions related to cytoskeletal dynamics, vesicle trafficking and synaptic physiology whereas CRMP2 functions in adult brain are still being elucidated. CRMP2 has been associated with several neuropathologic or psychiatric conditions including Alzheimer's disease (AD) and schizophrenia, either at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
183
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(186 citation statements)
references
References 72 publications
3
183
0
Order By: Relevance
“…In addition to its canonical roles in neurite outgrowth, the web of interactions characterized now for CRMP-2 with motor proteins, kinases, channels, receptors, enzymes, and endocytosis-exocytosis related proteins suggests that CRMP-2 may serve as adaptors/ scaffold molecules and as traffic 'cops' [9]. Our laboratory has championed CRMP-2 as an important determinant of synaptic transmission [11][12][13]17,18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to its canonical roles in neurite outgrowth, the web of interactions characterized now for CRMP-2 with motor proteins, kinases, channels, receptors, enzymes, and endocytosis-exocytosis related proteins suggests that CRMP-2 may serve as adaptors/ scaffold molecules and as traffic 'cops' [9]. Our laboratory has championed CRMP-2 as an important determinant of synaptic transmission [11][12][13]17,18].…”
Section: Discussionmentioning
confidence: 98%
“…Initially identified in chick sensory neurons as a protein responsible for growth cone retraction in response to negative guidance signals in the semaphorin 3A (Sema3A) pathway [1], CRMP-2 analogues were subsequently identified in Caenorhabditis elegans (uncoordinated protein-33 (Unc-33)) [2], in rodents ((named turned on after development 64 (TOAD-64)) in rats and Unc-33 like phosphoprotein (Ulip) in mice) [3][4][5], in humans (HUlip) [6,7] and in Drosophila Melanogaster [8]. Together with its established roles in neurite growth and retraction and kinesin-dependent axonal transport, mapping the CRMP-2 interactome has revealed previously unappreciated functions including affecting microtubule dynamics, protein endocytosis and vesicle recycling, as well as synaptic assembly (see reviews by Hensley [9] and Strittmatter [10]). …”
Section: Introductionmentioning
confidence: 99%
“…Hyperactive Cdk5-p25 hyperphosphorylates tau (also known as MAPT), which aggregates to form the neurofibrillary tangles observed in Alzheimer's disease. Furthermore, hyperphosphorylation of tau and CRMP2 (also known as DPYSL2) by Cdk5 also significantly impairs axonal transport, causing neuronal death (Hensley et al, 2011). Similarly, deregulation of Cdk5 by ectopic expression of p25 results in increased pausing of mitochondria in neurons (Morel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…PIPP Regulates Axon Polarity and Neurite Length-CRMP2 promotes axon/dendrite selection, axon growth cone retraction, and axon elongation (18,19). We have previously shown that PIPP inhibits neurite extension (16), but have not examined its distribution or function in axons or dendrites.…”
Section: Y2h Screening Identifies ␤Ii Tubulin and Crmp1 As Pippbindinmentioning
confidence: 99%
“…Here we identify PIPP interacting partners as CRMP2 and tubulin by Y2H screening of brain libraries. CRMP2 is a neuronal adaptor protein that interacts with many binding partners, promoting axon polarity, neurite outgrowth, and elongation (18,19). PIPP and CRMP2 both independently bind ␤-tubulin and form a multiprotein complex with the motor protein, Kinesin-1.…”
mentioning
confidence: 99%